The prediction model for intraoperatively acquired pressure injuries in orthopedics based on the new risk factors: a real-world prospective observational, cross-sectional study - Li, Ning; Cui, Dalei; Shan, Li; Li, Haixia; Feng, Xuelian; Zeng, Huilan; Li, Lezhi (Frontiers in Physiology, 2023)
validity (area under the ROC curve= 0.77), which is expected to benefit clinical patients.In conclusion, we successfully identified new independent risk factors for IAPI-related injury in orthopedic patients and developed a clinical prediction model to serve as an important complement to existing scales and provide additional benefits to patients. Our study also suggests that a single measure is not sufficient for the prevention of IAPIs in orthopedic surgery patients and that a combination of measures may be required for the effective prevention of IAPI.